2022
DOI: 10.3390/biomedicines10071564
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pro/Antioxidant Imbalance in Blood of Women with Polycystic Ovary Syndrome Based on Determination of Oxidized Low-Density Lipoproteins and Ferric Reducing Ability of Plasma Values

Abstract: We investigated selected pro/antioxidant parameters in a group of women with polycystic ovary syndrome (PCOS) divided according to age, body mass index (BMI), waist-to-hip ratio (WHR), homeostatic model assessment for insulin resistance (HOMA-IR) and quantitative insulin sensitivity check index (Quicki). We chose oxidized low-density lipoproteins (oxLDL-C) as a marker of oxidative stress and the ferric reducing ability of plasma (FRAP) as a marker of antioxidant status. In women with PCOS, the values of BMI, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Finally, the lack of lipid profile and inflammatory markers may be a further limitation of our study. However, it is well known that patients with PCOS often have abnormal lipid levels, and chronic low-grade systemic inflammation is an important factor in this disease [ 6 , 14 , 33 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the lack of lipid profile and inflammatory markers may be a further limitation of our study. However, it is well known that patients with PCOS often have abnormal lipid levels, and chronic low-grade systemic inflammation is an important factor in this disease [ 6 , 14 , 33 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is one of the most common endocrinopathies and its prevalence—depending on the adopted diagnostic criteria and the population studied—ranges from 4 to 16% of reproductive-age women [ 1 , 2 , 3 ]. Characteristic features of the syndrome include menstrual disorders, hyperandrogenism, and often obesity and infertility [ 4 , 5 , 6 ]. In addition to primary and secondary infertility, pregnancy complications are more common in this patient group, including gestational diabetes, hypertension, preeclampsia, and a higher risk of miscarriage or low-birth-weight offspring [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…FRAP was measured in diluted serum (10-fold in PBS) using the colorimetric method with ferric tripyridyltriazine described earlier [ 30 ]. The FRAP reagent was prepared by mixing 300 mM of acetate buffer, with a pH of 3.6, with 10 mM of 2,4,6-tripyridyl-s-triazine (TPTZ) (Cat.…”
Section: Methodsmentioning
confidence: 99%
“…They proposed AIP and Castelli Index as atherogenicity additional indicators to assess the risk of cardiometabolic diseases in PCOS in order to rapidly identify risk groups among this population. Niepsuj et al [15] took into account further parameters, such as oxidized low-density lipoproteins (oxLDL-C) and the ferric-reducing ability of plasma (FRAP), to evaluate pro/anti antioxidant imbalance blood in PCOS patients. This clinical study found a significant association between oxLDL concentration and the FRAP value, and selected hormonal and metabolic parameters in the PCOS course.…”
mentioning
confidence: 99%